L’espace public - Marie-Gabrielle Suraud (Communication)
From the empirical case constituted by the regional debate organized after the explosion of the AZF chemical plant in Toulouse on September 21, 2001, this study takes on the question of the evolution of democratic practices by concentrating on the analysis of the relationship between modes of civic participation in the mechanisms of consultation and of the structuration of autonomous public space in civil society. Although these two fields of analysis are usually treated separately, this research aims, on the contrary, to put the question of the articulation between institutional spaces of debate and autonomous space of civil society at the heart of the reflection.